Analysis of salivary phenotypes of generalized aggressive and chronic periodontitis through nuclear magnetic resonance‐based metabolomics. Issue 12 (21st August 2018) - Romano, Federica; Meoni, Gaia; Manavella, Valeria; Baima, Giacomo; Tenori, Leonardo; Cacciatore, Stefano; Aimetti, Mario
Abstract: Background: Recent findings about the differential gene expression signature of periodontal lesions have raised the hypothesis of distinctive biological phenotypes expressed by generalized chronic periodontitis (GCP) and generalized aggressive periodontitis (GAgP) patients. Therefore, this cross‐sectional investigation was planned, primarily, to determine the ability of nuclear magnetic resonance (NMR) spectroscopic analysis of unstimulated whole saliva to discriminate GCP and GAgP disease‐specific metabolomic fingerprint and, secondarily, to assess potential metabolites discriminating periodontitis patients from periodontally healthy individuals (HI). Methods: NMR‐metabolomics spectra were acquired from salivary samples of patients with a clinical diagnosis of GCP ( n  = 33) or GAgP ( n  = 28) and from HI ( n  = 39). The clustering of HI, GCP, and GAgP patients was achieved by using a combination of the Principal Component Analysis and Canonical Correlation Analysis on the NMR profiles. Results: These analyses revealed a significant predictive accuracy discriminating HI from GCP, and discriminating HI from GAgP patients (both 81%). In contrast, the GAgP and GCP saliva samples seem to belong to the same metabolic space (60% predictive accuracy). Significantly lower levels ( P  < 0.05) of pyruvate, N ‐acetyl groups and lactate and higher levels ( P  < 0.05) of proline, phenylalanine, and tyrosine were found in GCP and GAgP patients compared with HI. Conclusions: Within the limitations of this study, CGP and GAgP metabolomic profiles were not unequivocally discriminated through a NMR‐based spectroscopic analysis of saliva.